Application of AHP Method in The Decision Support System for Determining the Best Early Childhood Education (PAUD) by Education Office of Bengkulu City - Novita Sari; Maryaningsih Maryaningsih; Jhoanne Fredricka (Penerbit Jurnal Indonesia, 2021)
Early Childhood Education (PAUD) is education to help physical and spiritual growth and development so that children have readiness to enter further education, which is held on formal, non-formal, and informal. In determining Best Early Childhood Education there are criteria from Education and Cultural Office Bengkulu City, namely there are six criteria, including Accreditation, Curriculum, Facilities, Tuition Fees, Number of Teachers, Number of Students. The research method used is the Analytical Hierarchy Process (AHP) method. AHP can assist in making decisions on complex issues by simplifying the process. This system can assist decision makers in determining the best Early Childhood Education quickly and accurately. It is hoped that later this application will be able to use this application in determining the Best Early Childhood Education at Education and Cultural Office Bengkulu City, as well as maintenance of the application that the writer has previously made so that in the future it can be used by Education and Cultural Office Bengkulu City.